Madrasah al-Maarif al-Wathaniyah, Artikulasi Pembaharuan Pendidikan Islam Haji Sulong di Patani - Chesueni, Solahuddeen; Baheem, Nur Alfan; Lohmi, Daneeya; Nugroho, Taufik; Nadjih, Difla; Ha, Ibroheem (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
This study aims to explore information on the life of Haji Sulong in the field of Islamic Education, especially the renewal of educational institutions. As for the benefits of this research, apart from adding to the scientific literature in the field of history, it is also useful as a lesson for the current generation of Thai Muslims regarding Islamic education with the concept of Thai nationalism. In historical studies, it can be seen that he renewed traditional education into madrasas that the people in Patani could feel the benefits of even though in a short time because of the closure by the government.